Locks of hair and quill pens - Hummel, Betty, 1793-1883 (collector)::::::::::::::: (2023)
Framed object including thirteen locks of hair attributed to Beethoven, Goethe, the Grand Duchess Maria Pavlovna of Russia, Princess Adelaide of Saxe-Meiningen, Duchess Amalia of Saxony-Weimar, and eight members of the Hummel family, along with two quill pens attributed to Beethoven and Johann Gottfried Herder, and two laurel leaves from a wreath placed in Beethoven's grave by J. N. Hummel during his burial on March 29, 1827. With a key to the objects inside the frame written by Betty Hummel on the back.